Stable isotope labelling methods in mass spectrometry-based quantitative proteomics - Chahrour, Osama; Cobice, Diego; Malone, John (Journal of pharmaceutical and biomedical analysis, 2015)
•Complementary ICP-MS application in proteomics for absolute protein quantification.•Summarising the pros and cons of stable isotope labelling methods in mass spectrometry.•Explaining novel Isobaric peptide termini labelling (IPTL).•Reviewing OxICAT (oxidation state determination using ICAT).•Reviewing the Tandem Mass Tag Reagent family. Mass-spectrometry based proteomics has evolved as a promising technology over the last decade and is undergoing a dramatic development in a number of different areas, such as; mass spectrometric instrumentation, peptide identification algorithms and bioinformatic computational data analysis. The improved methodology allows quantitative measurement of relative or absolute protein amounts, which is essential for gaining insights into their functions and dynamics in biological systems. Several different strategies involving stable isotopes label (ICAT, ICPL, IDBEST, iTRAQ, TMT, IPTL, SILAC), label-free statistical assessment approaches (MRM, SWATH) and absolute quantification methods (AQUA) are possible, each having specific strengths and weaknesses. Inductively coupled plasma mass spectrometry (ICP-MS), which is still widely recognised as elemental detector, has recently emerged as a complementary technique to the previous methods. The new application area for ICP-MS is targeting the fast growing field of proteomics related research, allowing absolute protein quantification using suitable elemental based tags. This document describes the different stable isotope labelling methods which incorporate metabolic labelling in live cells, ICP-MS based detection and post-harvest chemical label tagging for protein quantification, in addition to summarising their pros and cons.